Numerical investigation of the aerodynamic breakup of droplets in tandem. (April 2019) - Stefanitsis, Dionisis; Malgarinos, Ilias; Strotos, George; Nikolopoulos, Nikolaos; Kakaras, Emmanouil; Gavaises, Manolis
Highlights: Numerical examination of the aerodynamic breakup of four Diesel droplets in tandem formation at representative engine conditions. Identification of a new breakup mode in the multi-mode regime, termed as "shuttlecock". Droplet proximity becomes important for non-dimensional distances between the droplets lower than 9. Drag coefficient and liquid surface area of the "representative chain droplet" are lower than the corresponding ones of the isolated droplet; breakup initiation time is longer and the critical We number is higher. Proposed correlations to predict the drag coefficient, liquid surface area, breakup initiation time and critical We of the "representative chain droplet". Abstract: The present work examines the aerodynamic breakup of four liquid droplets in tandem formation at Diesel engine conditions using the Volume of Fluid (VOF) method. The examined Weber ( We ) numbers range from 15 up to 64 and the non-dimensional distances between the droplet centres ( L/D0 ) vary from 1.25 up to 20. Focus is given on the breakup process of the third droplet of the row, which is regarded as a "representative chain droplet"; its development is compared against that of an isolated droplet at the same flow conditions. It is found that for small distances and depending on the We number, the obtained shapes and breakup modes between the droplets are different, with the representative chain droplet experiencing a new breakup mode in the multi-mode regime, termed as "shuttlecock". This is characterized by an oblique peripheral stretching of the droplet caused by the acting of pressure forces at an off-centre region. Moreover, the drag coefficient and liquid surface area of the representative chain droplet are lower than the corresponding ones of the isolated droplet, while the breakup initiation time is longer and the minimum We number required for breakup (critical We ) is higher; correlations are provided to quantify the effect of droplet distance on the aforementioned quantities. Generally, the droplet proximity becomes important for L/D0 < 9. Finally, the predicted drag coefficient is utilised in a simplified 0-D model that is capable of estimating the temporal evolution of droplet velocity of the representative chain droplet.